A metal alloy catalyst and its preparation method and application

By preparing the metal alloy catalyst Ni/MOx-SDC/Al2O3 with nanosheet layered structure, the problem of existing catalysts being deactivated under high temperature conditions and limited activation and conversion under low temperature conditions is solved, and efficient carbon dioxide methanation under low temperature conditions is achieved, with good catalytic performance and stability.

CN116273043BActive Publication Date: 2025-04-01TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310180581.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-04-01
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

The existing carbon dioxide methanation catalysts are prone to inactivate under high temperature conditions, and the activation and conversion of carbon dioxide under low temperature conditions is limited, making it difficult to achieve efficient carbon dioxide resource utilization.

Method used

The metal alloy catalyst Ni/MOx-SDC/Al2O3 with a nanosheet-like structure was prepared by hydrothermal method and reduction method. The oxide of metal M was introduced using SDC/Al2O3 as a support to form a catalyst with good catalytic properties.

Benefits of technology

The carbon dioxide conversion rate was significantly improved under low temperature conditions, and it had nearly 100% selectivity to the target product methane, and the catalyst had good stability and practicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116273043B_ABST
    Figure CN116273043B_ABST
Patent Text Reader

Abstract

The invention discloses a metal alloy catalyst having a molecular formula of Ni / MO x ‑SDC / Al2O3, with SDC / Al2O3 as carrier, and MO x The metal alloy catalyst is an oxide of metal M; the metal alloy catalyst has a nanosheet layer structure. The metal alloy catalyst has good catalytic performance, significantly improves the carbon dioxide conversion rate under low temperature conditions, and can also make the target product methane have nearly 100% selectivity. The present invention also provides a preparation method and application of the metal alloy catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts, and in particular to a metal alloy catalyst and a preparation method and application thereof. Background Art

[0002] As the main component of greenhouse gases, carbon dioxide has caused a series of environmental problems such as greenhouse effect and global warming. Therefore, reducing its emissions is an urgent problem to be solved. With the vigorous development of the global carbon trading market and the continuous improvement of the carbon trading system, coupled with my country's responsibility as a major country to solve climate problems, it has also proposed the dual carbon goals of "carbon neutrality" and "carbon peak". To achieve this goal, the "capture, storage, and utilization (CCUS)" technology of carbon dioxide has received widespread attention. Among the various ways of utilization, resource utilization of carbon dioxide is easier to achieve than other ways. Natural gas plays a vital role in daily life and production. Converting carbon dioxide into natural gas and realizing the resource utilization of carbon dioxide will bring huge economic and environmental benefits.

[0003] The catalysts commonly used for carbon dioxide methanation reactions are mostly transition metals and precious metals loaded as active components on metal oxide carriers such as Al2O3, SiO2, TiO2, and CeO2. Among them, Rh and Ru show good activity, but they cannot be industrialized due to their small reserves and high prices. Nickel-based catalysts have been widely studied because of their reaction activity comparable to that of precious metal catalysts. However, the carbon dioxide methanation reactions reported at this stage are mostly carried out at high temperatures (300-450°C) and under relatively high pressure conditions, which will cause Ni metal particles to sinter, and the carbon deposits produced by side reactions will cover the surface of Ni particles to organize the contact between the active phase and the reactants, which will deactivate the catalyst. In addition, the reaction is thermodynamically an exothermic reaction, and a large amount of heat will be released after the reaction, which will accelerate the deactivation of the catalyst. The above series of problems can be alleviated to a large extent at low temperatures, but due to the chemical inertness and thermodynamic stability of carbon dioxide molecules, their activation and conversion at low temperatures will be greatly limited. Therefore, there is an urgent need for a catalyst that can be used for carbon dioxide methanation with good catalytic performance and high stability. Summary of the invention

[0004] Therefore, the purpose of the present invention is to solve the above problems and to provide a metal alloy catalyst and a preparation method and application thereof.

[0005] The present invention provides a metal alloy catalyst having a molecular formula of Ni / MO x -SDC / Al2O3, with SDC / Al2O3 as carrier, and MO x is an oxide of metal M;

[0006] The metal alloy catalyst has a nanosheet layered structure.

[0007] Furthermore, the content of Ni is 5-30wt%.

[0008] Furthermore, the metal M is one or more of Mn, Pt, Fe, Co, Cu, Ru, and Rh.

[0009] Furthermore, in the metal alloy catalyst, the ratio of trivalent cations to the sum of divalent cations and trivalent cations is 0.17-0.33.

[0010] The present invention also provides a method for preparing a metal alloy catalyst, comprising:

[0011] Prepare alkaline solution: fully dissolve soluble carbonate to obtain solution A, and fully dissolve strong base to obtain solution B;

[0012] Synthesize metal oxide precursor: Ni 2+ Soluble salts containing metal elements M, soluble salts containing Ce 3+ Soluble salts containing Sm 3+ Soluble salts containing Al 3+ The soluble salt is fully dissolved to obtain solution C; solution C is added to solution A, and solution B is added to adjust the pH to 10-13 to obtain solution D; solution D is used to perform a hydrothermal reaction to obtain a hydrothermal product, and the hydrothermal product is washed, dried, and then calcined to obtain a metal oxide precursor;

[0013] Reduction: The metal oxide precursor can be reduced with H2 to obtain the desired metal alloy catalyst.

[0014] Furthermore, the Ni 2+ Soluble salts containing metal elements M, soluble salts containing Ce 3+ Soluble salts containing Sm 3+ Soluble salts containing Al 3+ The molar ratio between the soluble salts is 1:(0.1-0.3):(0.2-0.4):(0.2-0.4):(0.2-0.4).

[0015] Furthermore, the temperature of the hydrothermal reaction is 100-150° C. and the time is 15-30 hours.

[0016] Furthermore, the calcination temperature is 450-550°C, the heating rate is 1-2°C / min, and the calcination time is 3-5h.

[0017] Furthermore, the reduction temperature is 500-600° C. and the time is 2-4 hours.

[0018] The present invention also provides an application of a metal alloy catalyst, wherein the metal alloy catalyst is applied to carbon dioxide methanation.

[0019] The above technical solution of the present invention can synthesize a nanosheet-shaped metal alloy catalyst, which has excellent catalytic performance, significantly improves the carbon dioxide conversion rate under low temperature conditions, and can also make the target product methane have nearly 100% selectivity, and the metal alloy catalyst has both good stability and practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein

[0021] Figure 1 This is the XRD pattern of the precursor before calcination in experimental group 1.

[0022] Figure 2 This is the TG-DTG spectrum of the precursor before calcination in experimental group 1.

[0023] Figure 3 This is the XRD pattern of the metal oxide precursor in experimental group 2.

[0024] Figure 4 This is the SEM image of the metal oxide precursor in experimental group 2.

[0025] Figure 5 This is the BET diagram of the metal oxide precursor in experimental group 2.

[0026] Figure 6 This is the XRD pattern of the metal alloy catalyst in experimental group 3.

[0027] Figure 7 This is the SEM image of the metal alloy catalyst in experimental group 3.

[0028] Figure 8 This is the catalyst stability test diagram of test group 3.

[0029] Fig. 9 This is the XRD pattern of the catalyst after the stability test of test group 3. DETAILED DESCRIPTION

[0030] The following embodiments are only preferred technical solutions of the present invention and are not intended to limit the present invention in any way. For those skilled in the art, the present invention may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should all be included in the protection scope of the present invention.

[0031] Embodiment 1

[0032] A method for preparing a metal alloy catalyst comprises:

[0033] Step S1: preparing an alkaline solution: fully dissolving a soluble carbonate to obtain a solution A, and fully dissolving a strong base to obtain a solution B;

[0034] Step S2: Synthesis of metal oxide precursor: 2+ Soluble salts containing metal elements M, soluble salts containing Ce 3+ Soluble salts containing Sm 3+ Soluble salts containing Al 3+ The soluble salt is fully dissolved to obtain solution C; solution C is added to solution A, and solution B is added to adjust the pH to 10-13 to obtain solution D; solution D is used to perform a hydrothermal reaction to obtain a hydrothermal product, and the hydrothermal product is washed, dried, and then calcined to obtain a metal oxide precursor;

[0035] Step S3: Reduction: The metal oxide precursor is reduced with H2 to obtain the desired metal alloy catalyst.

[0036] The preparation method of the catalyst can synthesize a nano-sheet metal alloy catalyst. The metal alloy catalyst has excellent catalytic performance, significantly improves the carbon dioxide conversion rate under low temperature conditions, and can also make the target product methane have nearly 100% selectivity. In addition, the metal alloy catalyst has both good stability and practicality.

[0037] By introducing cerium salt and samarium salt, metallic samarium (Sm) was doped into CeO2 to form Sm 0.2 Ce 0.8 O 1.9 (SDC), SDC is doped into Al2O3 to modify it and then form the modified support SDC / Al2O3; on the one hand, cerium oxide (CeO2) has a reversible Ce 3+ / Ce 4+ Redox pairs, and the surface has abundant controllable oxygen vacancies and acidity. Oxygen vacancies play an extremely important role as key intermediates in the formation of bidentate carbonates, and oxygen vacancies are also the most active sites for CO2 adsorption. A large number of oxygen vacancies increase the migration rate of lattice oxygen, which is kinetically beneficial to the direct dissociation of CO2 and can also improve the conversion rate of CO2. On the other hand, the doping of samarium metal can well promote the further hydrogenation of formate to generate CH4.

[0038] In step S1, the soluble carbonate may be sodium carbonate or potassium carbonate, preferably sodium carbonate; the strong base may be sodium hydroxide or potassium hydroxide, preferably sodium hydroxide, and further, the concentration of solution B is 1-2 mol / L.

[0039] In step S2, preferably, the element M can be one or more of Mn, Pt, Fe, Co, Cu, Ru, and Rh, preferably Mn. The soluble salt containing the metal element M can be at least one of nitrate, sulfate, and chloride, that is, when M is Mn, it can be one or a mixture of manganese nitrate, manganese sulfate, and manganese chloride; the concentration of the soluble salt is preferably 0.0025-0.0075 mol / L.

[0040] Metal Al 3+ The soluble salt may be one or a mixture of aluminum nitrate, aluminum sulfate, and aluminum chloride; the concentration of the soluble salt is preferably 0.0002-0.0006 mol / L.

[0041] Preferably, the Ni 2+ Soluble salts containing metal elements M, soluble salts containing Ce 3+ Soluble salts containing Sm 3+ Soluble salts containing Al 3+ The molar ratio of the soluble salts is 1:(0.1-0.3):(0.2-0.4):(0.2-0.4):(0.2-0.4). By determining the dosage ratio, the structure and performance of the synthesized catalyst can be better guaranteed.

[0042] The adding of solution C into solution A is preferably done dropwise, that is, solution C is added dropwise into solution A. Furthermore, solution B is added to adjust the pH to 11.

[0043] Preferably, the temperature of the hydrothermal reaction is 100-150° C., and the time is 15-30 h; in some preferred embodiments, the temperature of the hydrothermal reaction is 120° C., and the time is 12 h.

[0044] Preferably, the calcination temperature is 450-550°C, the heating rate is 1-2°C / min, and the calcination time is 3-5h. In some preferred embodiments, the calcination temperature is 500°C, the heating rate is 2°C / min, and the time is 3h.

[0045] Step S2 can specifically be, dissolving nickel nitrate, manganese nitrate, cerium nitrate, samarium nitrate, and aluminum nitrate solutions together to form solution C, adding solution C dropwise into solution A, and combining with solution B so that the pH is stabilized at 11 to obtain solution D, placing solution D in a hydrothermal kettle, and performing a hydrothermal reaction at 120°C for 12 hours to obtain a hydrothermal product, washing the hydrothermal product, centrifuging it, drying it at 80°C for 10 hours, and then heating it to 500°C at a heating rate of 2°C / min, and calcining it for 3 hours to obtain a metal oxide precursor.

[0046] In step S3, the reduction temperature is preferably 500-600°C, the reduction time is preferably 2-4 hours, and further, the reduction temperature is 550°C, and the reduction time is 2 hours. The hydrogen concentration in the reduction environment is preferably 60%-100%.

[0047] Embodiment 2

[0048] A metal alloy catalyst can be prepared by using the preparation method of the metal alloy catalyst provided in Example 1.

[0049] The metal alloy catalyst has the molecular formula Ni / MO x -SDC / Al2O3, with SDC / Al2O3 as carrier, and MO x is an oxide of metal M; the morphology of the metal alloy catalyst is a nanosheet layered structure. SDC / Al2O3 is a modified alumina carrier, SDC is Sm 0.2 Ce 0.8 O 1.9 .

[0050] This metal alloy catalyst has excellent catalytic performance, significantly improves the carbon dioxide conversion rate under low temperature conditions, and can also achieve nearly 100% selectivity for the target product methane. In addition, this metal alloy catalyst has both good stability and practicality.

[0051] On the one hand, cerium oxide (CeO2) has a reversible Ce 3+ / Ce 4+ Redox pairs, and the surface has abundant controllable oxygen vacancies and acidity. Oxygen vacancies play an extremely important role as key intermediates in the formation of bidentate carbonates, and oxygen vacancies are also the most active sites for CO2 adsorption. A large number of oxygen vacancies increase the migration rate of lattice oxygen, which is kinetically beneficial to the direct dissociation of CO2 and can also improve the conversion rate of CO2. On the other hand, the doping of samarium metal can well promote the further hydrogenation of formate to generate CH4.

[0052] Preferably, the content of Ni is 5-30wt%. Preferably, the metal M can be one or more of Mn, Pt, Fe, Co, Cu, Ru, and Rh. In some preferred embodiments, the metal M is Mn, that is, the molecular formula of the metal alloy catalyst is Ni / MO x -SDC / Al2O3.

[0053] Preferably, in the metal alloy catalyst, the ratio of trivalent cations to the sum of divalent cations and trivalent cations is 0.17-0.33; for example, when the metal M is Mn, Al 3+ 、Ce 3+ 、Sm 3+ Account for Ni 2+ , Mn 2+ 、Ce 3+ 、Sm 3+ 、Al3 + The total ratio is 17%-33%. This will form a good LDHs structure.

[0054] Embodiment 3

[0055] An application of a metal alloy catalyst is to apply the metal alloy catalyst provided in Example 2 to carbon dioxide methanation, and is particularly suitable for carbon dioxide methanation reaction under low temperature conditions, where the low temperature refers to 200-400°C.

[0056] Embodiment 4

[0057] A method for converting carbon dioxide into methane comprises contacting carbon dioxide and hydrogen with the metal alloy catalyst of Example 2 for reaction under the reaction conditions of carbon dioxide methanation.

[0058] Preferably, the contact reaction is carried out in a fixed bed reactor. The reaction conditions are that the ratio of CO2 to H2 is 1:2-4, the reaction temperature is 200-400°C, and the reaction pressure is normal pressure. Normal pressure here refers to one atmosphere, i.e. 1 bar.

[0059] Some specific experimental groups and test / characterization results are provided below

[0060] Experimental Group 1

[0061] Take 3.98g of anhydrous sodium carbonate and dissolve it in deionized water to obtain the required solution A, then take 6g of NaOH and dissolve it in deionized water to obtain 1.5mol / L solution B.

[0062] Dissolve 3.63g Ni(NO3)2·6H2O, 0.63g Mn(NO3)2·4H2O, 0.17g Ce(NO3)3·6H2O, 0.18g Sm(NO3)3·6H2O, and 1.58g Al(NO3)3·9H2O in deionized water, stir for 30 minutes to fully dissolve the salt solution, and obtain solution C; add solution C dropwise to the above solution A, and add the prepared solution B, maintain the pH at 11, and stir vigorously for 0.5-1h to obtain solution D, pour solution D into a polytetrafluoroethylene liner, and then place the liner in a stainless steel reactor for hydrothermal reaction at 120°C for 24h to obtain a precursor after hydrothermal reaction. Wash the precursor, centrifuge it, and place it in an oven at 80°C to dry for 10h to obtain a precursor before calcination.

[0063] Experimental Group 2

[0064] The precursor before dry calcination obtained in Experimental Group 1 was placed in a muffle furnace and calcined at 500° C. for 3 h at a heating rate of 2° C. / min to obtain a metal oxide precursor.

[0065] Experimental Group 3

[0066] The metal oxide precursor obtained in Experimental Group 2 was reduced with H2 at 550°C for 2h to obtain the desired metal alloy catalyst.

[0067] The following tests / characterizations are performed for the above experimental groups

[0068] 1. Characterization of the precursor before calcination obtained in experimental group 1

[0069] Figure 1 is the XRD pattern of the precursor before calcination in Experimental Group 1. Figure 1 It can be seen that the characteristic peaks at 11.3°, 22.7°, 34.4°, 38.8°, 46.3°, 61.3° and 62.7° are respectively attributed to the (003), (006), (012), (018), (110) and (113) crystal planes of LDHs, proving that the LDHs structure was successfully synthesized.

[0070] Figure 2 This is the TG-DTG spectrum of the precursor before calcination in experimental group 1. Figure 2 The weight loss and weight loss rate of the LDHs precursor are shown in Figure 2, indicating that the samples are transformed into the corresponding metal oxides at 500 °C.

[0071] 2. Characterization of the metal oxide precursor obtained in Experimental Group 2

[0072] Figure 3 is the XRD pattern of the metal oxide precursor in Experimental Group 2. Figure 3 It can be seen that a strong peak appears at 28.4°, which is attributed to the (111) crystal plane of SDC. Meanwhile, the peaks at 37.2°, 43.3°, 62.9°, and 75.4° can be attributed to the (111), (200), (220), and (311) crystal planes of NiO.

[0073] Figure 4 This is the SEM image of the metal oxide precursor in Experimental Group 2. It can be seen that the morphology of the metal oxide precursor is a nanosheet structure.

[0074] Figure 5 is the BET diagram of the metal oxide precursor in Experimental Group 2. Figure 5 It can be seen that its adsorption-desorption isotherm is type IV, and an H2-type hysteresis loop appears, indicating that there is a mesoporous structure in the catalyst.

[0075] 3. Metal alloy catalyst Ni / MnO obtained in experimental group 3 x -SDC / Al2O3 characterization

[0076] Figure 6 This is the XRD pattern of the metal alloy catalyst in experimental group 3.

[0077] Figure 6 The peak intensity corresponding to the SDC structure of the reduced catalyst is weakened, which indicates that MnO x There is a certain degree of interaction between MnO and SDC, and the interaction between the two will promote x The redox property of Mn 4+ Reduced to Mn 2.3+ More oxygen vacancies are formed, and the increase in oxygen vacancies is conducive to the activation of CO2, which makes the reaction proceed better; due to the low content of Mn, no MnO x The corresponding peak.

[0078] Figure 7 This is the SEM image of the metal alloy catalyst in experimental group 3.

[0079] Figure 7 It is shown that the reduced catalyst still has a nanosheet structure without major changes, indicating that the reduced catalyst is relatively stable in structure.

[0080] 4. Conduct stability test on catalyst

[0081] A fixed bed reactor was used to study the catalytic performance of the catalyst prepared in Experimental Group 3. The fixed bed reactor had an inner diameter of 10 mm and a length of 560 mm. The reactants and products were detected by a gas chromatograph equipped with a thermal conductivity detector (TCD) and a soap bubble flowmeter.

[0082] Reaction conditions: 0.2 g of catalyst mixed with 5 g of quartz sand was loaded into the constant temperature zone of the fixed bed reactor, heated to 200 °C under Ar atmosphere, switched to a mixed gas of CO2:H2=1:4, with a flow rate of 50 mL / min, and the reaction pressure was normal pressure, where normal pressure refers to one atmosphere, i.e. 1 bar.

[0083] Test Group 2-9

[0084] The difference from test group 1 is that the temperature is raised to 225°C, 250°C, 275°C, 300°C, 325°C, 350°C, 375°C, and 400°C under Ar atmosphere.

[0085] Figure 8 This is a catalyst stability test diagram for test group 3. The catalyst did not show obvious deactivation during the 100-hour test, and the CH4 selectivity was basically maintained at 100%, indicating that the catalyst has good catalytic performance.

[0086] Table 1 is obtained based on the test data of test groups 1-9:

[0087] Table 1 Effect of different reaction temperatures on Ni / MnO x - Effect of SDC / Al2O3 Metal Alloy Catalyst on CO2 Methanation

[0088]

[0089] It can be seen from Table 1 that the catalyst synthesized by the present invention can also achieve a high carbon dioxide conversion rate and a methane selectivity of nearly 100% under low temperature conditions. The carbon dioxide conversion rate and methane selectivity can reach 88.01% and 100% at 250°C.

[0090] Further characterization of the catalyst after stability testing in test group 3

[0091] Fig. 9 This is the XRD diagram of the catalyst after the stability test of test group 3. It can be seen from the figure that there is no obvious difference between the catalyst after 100 hours of reaction and after reduction, indicating that the catalyst structure is stable.

[0092] In summary, the nickel-based metal alloy catalyst prepared by the present invention is well suited for carbon dioxide methanation reaction under low temperature conditions. It can stably maintain a high carbon dioxide conversion rate and almost 100% methane selectivity at 250°C, and has good resistance to sintering and carbon deposition. In addition, the catalyst is simple to produce, low in cost, and easy to industrialize.

[0093] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0094] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A metal alloy catalyst, characterized in that: The molecular formula is Ni / MO x -SDC / Al2O3, with SDC / Al2O3 as carrier, and MO x is an oxide of metal M, wherein the metal M is Mn, and SDC is Sm 0.2 Ce 0.8 O 1.9 ; The morphology of the metal alloy catalyst is a nanosheet layered structure; The metal alloy catalyst is prepared by the following method: Prepare alkaline solution: fully dissolve soluble carbonate to obtain solution A, and fully dissolve strong base to obtain solution B; Synthesize metal oxide precursor: Ni 2+ Soluble salts containing metal elements M, soluble salts containing Ce 3+ Soluble salts containing Sm 3+ Soluble salts containing Al 3+ The soluble salt is fully dissolved to obtain solution C; Solution C was added to solution A, and solution B was added to adjust the pH to 10-13 to obtain solution D; Using solution D to perform a hydrothermal reaction to obtain a hydrothermal product, washing the hydrothermal product, drying it, and then calcining it to obtain a metal oxide precursor; The Ni 2+ Soluble salts containing metal elements M, soluble salts containing Ce 3+ Soluble salts containing Sm 3+ Soluble salts containing Al 3+ The molar ratio between the soluble salts is 1:(0.1-0.3):(0.2-0.4):(0.2-0.4):(0.2-0.4); Reduction: The metal oxide precursor can be reduced with H2 to obtain the desired metal alloy catalyst.

2. The metal alloy catalyst according to claim 1, characterized in that: The content of Ni is 5-30wt%.

3. The metal alloy catalyst according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 100-150° C. and the time is 15-30 hours.

4. The metal alloy catalyst according to claim 3, characterized in that: The calcination temperature is 450-550° C., the heating rate is 1-2° C. / min, and the calcination time is 3-5 hours.

5. The metal alloy catalyst according to any one of claims 1 to 4, characterized in that: The reduction temperature is 500-600° C. and the time is 2-4 hours.

6. An application of a metal alloy catalyst, characterized in that: The metal alloy catalyst according to any one of claims 1 to 5 is used for carbon dioxide methanation.